Politics of the Nobility: The Study of Growing Capital Andi in the Mayor`s Election of Palopo 2013-2018 - Samsul Samsul; Zuli Qodir (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
The purpose of this research is to find out what causes the weakening of the capital of Andi's nobility in Palopo City in the selection of candidates for mayor and what is the role of Andi's nobility in political contestation. This type of research is descriptive qualitative. The results showed that the capital owned by Andi's aristocracy in Palopo City was. First, the social capital built by Andi's nobility had not been carried out in a structured way from relations with the general public, community leaders, with community organizations, to officials in the bureaucracy and most importantly, Political parties. Second, economic capital is an important thing that used in the Mayor Election contestation in the City of Palopo, Bangsawan Andi figure who escaped as a candidate for mayor does not yet have sufficient capital in terms of funds. Third, the cultural capital owned by Bangsawan Andi, who escaped as a candidate for mayor, still lacked a high bargaining value in political contestation in Palopo City. Fourth, the Symbolic Capital is a capital that sufficiently calculated in the mayor election dispute in Palopo City, namely the title of nobility obtained from the blood of the descendants of the Luwu kings, only it must be accompanied by other capital to elected in political contestation.